PRAGMATICS OF SILENCE AND PAUSE IN ENGLISH AND RUSSIAN DISCOURSE - Maulenbergenova Biybiayim Baxadurovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Communication is not solely about words and utterances; it also involves the strategic use of silence and pauses. These elements, though non-verbal, hold significant meaning and contribute to the flow of conversation in profound ways. Silence and pause can indicate a range of social functions, such as showing agreement or disagreement, signaling contemplation, or indicating power dynamics between speakers. However, the role of silence and pause can differ depending on cultural contexts and linguistic norms. The present article explores how silence and pause are used in communication, with a focus on English and Russian languages, which exhibit unique patterns in terms of these non-verbal communicative strategies.